E-Module Media Based on Flip Book Maker in the Basic Hair Trimming Course - Intan Witari; Rahmiati; Linda Rosalina; Muhammad Giatman (Jurnal Pendidikan Indonesia, 2024)
The use of conventional learning methods is still less than optimal in attracting students' interest in technical practical material. The Flip Book Maker-based e-Module is expected to be an effective solution because it is able to combine multimedia elements, such as text, images, video and animation, which are presented interactively. This media not only increases student attraction and engagement, but also provides easy access and flexibility in the learning process. The main objective of this research is to develop and test the effectiveness of Flip Book Maker-based E-Module learning media in the Basic Hair Trimming course. This type of research is descriptive qualitative. This research focuses on developing a Flip Book Maker-based E-Module for the Basic Hair Trimming course using the Instructional Development Institute (IDI) model. The IDI model involves three stages: define, develop, and evaluate, ensuring a systematic approach to meeting educational needs. The data analysis method used is descriptive qualitative. The main results of this research show that the use of E-Module media based on Flip Book Maker in the Basic Hair Trimming course significantly improves the quality of learning. Based on effectiveness tests, students who use this E-Module show a better understanding of the material compared to conventional learning methods. Student learning outcomes increase, especially in aspects of technical skills and understanding complex hair trimming procedures. The implications of this research can be an innovative and effective alternative learning media in improving the quality of skills education.